Revolusi Islam Iran dan Pengaruhnya Bagi Perkembangan Syiah di Indonesia - Siti Fauziah (Tsaqofah, 2016)
Iran's 1979 Islamic revolution led by Ayatollah Khomeini, the Iranian nation has led to the establishment of the Islamic Republic of Iran. As the largest social revolution, the Islamic Revolution of Iran is not only to give effect to the Iranian nation but also have an impact and influence on Muslim communities across the world, including Indonesia. In Indonesia, the influence of the Iranian Revolution was not only influential in the rise of Muslims in Indonesia, but also led to the rapid development of Shia ideology in Indonesia. This is evident from the increasing proliferation of foundations of education, publishers, social organizations affiliated with Shia. Nevertheless Shiites in Indonesia is facing severe challenges, both internally in the form of a conflict between themselves and externally in the form of anti-Shia campaign carried out by the radical Salafi.